Intermediate Technology Development Group - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Give a man a fish, as the saying goes, and you are helping him for a very short while; teach him the art of fishing, and he can help himself all his life ... but teach him to make his own fishing tackle and you have helped him become not only...